Introgression Among Cultivated and Wild Grapevine in Tuscany - D’Onofrio, Claudio (Frontiers in Plant Science, 2020)
Wild grapevine, Vitis vinifera L. subsp. sylvestris (Gmelin, Hegi) is spontaneous to Europe and common in Tuscany. In this study, wild grapevines were identified in 22 populations from eight locations in Tuscan Maremma (Grosseto and Siena province). The plants were propagated by cuttings, collected in a vineyard, genotyped by nuclear simple sequence repeats (SSRs), chloroplast SSRs and single nucleotide polymorphisms (SNPs), and compared to locally-cultivated varieties (Vitis vinifera L. subsp. sativa) and to non-vinifera and non-vitis genotypes. The identity analysis revealed that some individuals were redundant genotypes, suggesting natural vegetative propagation. In addition, four of the supposed V.v. sylvestris were in fact naturalized V.v. sativa. The majority of putative sylvestris genotypes had chlorotype A, while the remainder had chlorotype D, as with the majority of Vitis vinifera subsp sativa cultivated in Italy. Some of the recovered sylvestris genotypes appeared to be natural crosses with cultivated grapevine varieties in Tuscany, and their chlorotype suggests a higher pollen flow from sativa to the sylvestris genotypes than in the opposite direction. In addition, other genotypes appeared to be crosses within sylvestris, sylvestris-sativa or sylvestris-sylvestris siblings, or equivalent relationships. These relationships suggest a noticeably level of sexual reproductive activities among sylvestris and sylvestris-sativa genotypes. A cluster and structure analysis clearly differentiated the true sylvestris from the sativa, and the non-vinifera or non-vitis genotypes, and also highlighted a possible introgression of sylvestris into some Italian and French cultivated varieties. The results therefore suggest that, in addition to the primary ancient center of domestication from the Near East to Central Asia, the introgression among cultivated and wild grapevine occurred in other centers of diversification along the migration routes, contributing to the domestication processes, and suggesting that these processes are still ongoing despite the reduction in populations of sylvestris. The results also highlight that the GrapeReSeq 18K Vitis genotyping chip are suitable for non-vitis genotyping and that the range of SNPs heterozygosity in sylvestris appears to be up to 6% less and does not overlap the heterozygosity range of sativa genotypes.